2018
DOI: 10.1101/394551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil bacterial biomass and diversity are affected by different furrow-ridge mulched management systems during potato continuous cropping

Abstract: 12The soil bacterial composition is vital for sustainable agriculture due to its 13 importance in biogeochemical processes in the soil environment. Multiple 14 management systems, such as different furrow-ridge mulched cropping systems, have 15 been established to reduce the damage caused by continuous cropping of potato 16 (Solanum tuberosum L.). However, little is known about the responses of soil 17 bacterial biomass and diversity to these systems. In this study, six different 18 ridge-furrow film planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…Other studies have compared potato microbiomes under different agricultural amendments, including biocontrol strategies 13 , 14 . The results of these potato microbiome studies show consistency with those reported for other crops with niche 11 , 12 , 14 , 15 , region 9 , 16 , and agricultural management 10 , 13 having significant effect on bulk soil, rhizosphere soil, and tuber microbiome profiles.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Other studies have compared potato microbiomes under different agricultural amendments, including biocontrol strategies 13 , 14 . The results of these potato microbiome studies show consistency with those reported for other crops with niche 11 , 12 , 14 , 15 , region 9 , 16 , and agricultural management 10 , 13 having significant effect on bulk soil, rhizosphere soil, and tuber microbiome profiles.…”
Section: Introductionsupporting
confidence: 83%
“…Although the clusters defined at the class or phylum level are difficult to identify some functions related to plant health can be inferred. Many bacterial taxa belonging to Vicinamibacterales have been implicated as plant growth promoting bacteria involved in the nitrogen cycle 10 , 31 . Species belonging to Burkholderiales have been reported as plant growth promoting bacteria related to phosphorous cycle 32 .…”
Section: Resultsmentioning
confidence: 99%